2020
DOI: 10.3389/fvets.2020.00150
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiota, Blood Metabolites, and Spleen Immunity in Broiler Chickens Fed Berry Pomaces and Phenolic-Enriched Extractives

Abstract: This study evaluated the performance, gut microbiota, and blood metabolites in broiler chickens fed cranberry and blueberry products for 30 days. A total of 2,800 male day-old broiler Cobb-500 chicks were randomly distributed between 10 diets: control basal diet; basal diet with bacitracin (BACI); four basal diets with 1 and 2% of cranberry (CP1, CP2) and blueberry (BP1, BP2) pomaces; and four basal diets supplemented with ethanolic extracts of cranberry (COH150, COH300) or blueberry (BOH150, BOH300) pomaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 62 publications
4
25
0
1
Order By: Relevance
“…Polyphenols may exert effects on gut morphology. Feeding broilers with essential oils containing polyphenols caused an increase in villus height in the duodenal section of the gut [52]. This report was also supported by another study that concluded that hesperidin, genistein, and some flavonoids from Ginkgo biloba leaves increased absorptive surfaces of the small intestine by modifying its length, crypt depth, and villus width in broilers with lipopolysaccharide stress [53].…”
Section: Gut Microbiota-polyphenols Interaction and Effects On Chickesupporting
confidence: 66%
“…Polyphenols may exert effects on gut morphology. Feeding broilers with essential oils containing polyphenols caused an increase in villus height in the duodenal section of the gut [52]. This report was also supported by another study that concluded that hesperidin, genistein, and some flavonoids from Ginkgo biloba leaves increased absorptive surfaces of the small intestine by modifying its length, crypt depth, and villus width in broilers with lipopolysaccharide stress [53].…”
Section: Gut Microbiota-polyphenols Interaction and Effects On Chickesupporting
confidence: 66%
“…Reque et al [13] and Tagliani et al [9] have positioned blueberry pomace, an industry by-product, as a valuable source of fiber with antioxidant capacity. Work performed by,Das et al [14] and Islam et al [15] have shown beneficial effects on intestinal health and immunity of including berry pomace as a broiler chicken feed additive., Juskiewicz et al [16] reported the effects of dietary dried fruit pomaces on turkey health while,Hassan et al [2] reviewed studies showing that grape pomace could be a promising feed additive as an antimicrobial alternative to antibiotic in livestock production.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our work examining the bioactivity of berry pomace and its application as an antibiotic alternative in poultry feed utilized berry pomace that had been freeze dried to remove water and obtain a shelf stable product. [14,15] Freeze drying is an effective drying method as materials undergoing freeze drying are not exposed to high temperatures, minimizing destruction of any bioactive compounds present. Despite the advantages freeze drying offers on product quality, long drying times and high operating costs are significant disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Starter (day 1–14), grower (14–28), and finisher (28–35) diets were formulated with wheat, barley, and corn as the principal cereals and soya meal as protein concentrates to meet the Cobb nutritional requirements. The detailed compositions for these diets were described in the article by Das et al. (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Pomaces are mass-produced as by-products from fruit processing, and they can be used as an alternative feedstuff to potentially replace antibiotics. Das et al. (2020) have reported that the supplementation of cranberry pomace ( CRP ) or blueberry pomace ( BLP ) significantly increased the body weight during the starting and growing phases and reduced the incidence of necrotic enteritis in commercial broilers.…”
Section: Introductionmentioning
confidence: 99%